A step past darkness - Kurian, Vera (Park Row Books, 2024)
"There's something sinister under the surface of the idyllic, suburban town of Wesley Falls, and it's not just the abandoned coal mine that lies beneath it. The summer of 1995 kicks off with a party in the mine where six high school students witness a horrifying crime that changes the course of their lives. The six couldn't be more different. Maddy, a devout member of the local megachurch. Kelly, the bookworm next door. James, a cynical burnout. Casey, a loveable football player. Padma, the shy straight-A student. Jia, who's starting to see visions she can't explain. When they realize that they can't trust anyone but each other, they begin to investigate what happened on their own. As tensions escalate in town to a breaking point, the six make a vow of silence, bury all their evidence, and promise to never contact each other again. Their plan works--almost. Twenty years later, Jia calls them all back to Wesley Falls--Maddy has been murdered, and they are the only ones who can uncover why. But to end things, they have to return to the mine one last time"--